Associations of Musculoskeletal Pain with Sociodemographic, Health Related, Reproductive Related, Pain Related, Treatment Seeking Pattern and Outcome Among Postmenopausal Women From Dhaka City - Rojina Akter; Abu Sayed Mohammad Giasuddin; Jasim Uddin; Md. Raisul Hassan (British Journal of Healthcare and Medical Research, 2026)
Background: The associations (correlations) of Musculoskeletal pain (MSP) with the presenting characteristics in postmenopausal women from Dhaka City are not known; Objectives: To determine the statistical significance of the associations of MSP with the presenting characteristics in postmenopausal women from Dhaka City; Materials & Methods: Statistically further analyses were done for associations of MSP with the presenting features reported in our descriptive cross-sectional study. The SPSS version 22.0 was used for the Chi-squared (c2) test on the previous results published; Results: MSP in the respondents i.e. postmenopausal women was strongly associated with age (p=0.005) and sunlight exposure (p=0.002), while it was not associated significantly with BMI (p=0.112), education level (p=0.707), age at onset of menopause (p=0.154) and number of children (p=0.778). Neck pain among the respondents was not significantly associated with age (p=0.515), BMI (p=0.574) and parenthesis (p=0.125). Shoulder pain was also not significantly associated with age (p=0.396), but it was significantly associated with stiffness (p=0.013). None of the factors studied were associated with low back pain significantly (p=0.173-0.759). But the knee pain was significantly dependent on sunlight exposure (p=0.019) and association of swelling in knee pain was significant (p=0.000). MSP and other symptoms were significantly improved after taking treatments (p=0.000); Conclusions: The implications of these observations relating various factors for MSP, neck pain, shoulder pain and treatments outcome in postmenopausal women were discussed.